Decompressive craniectomy in pediatric non-traumatic intracranial hypertension: a single center experience. (3rd May 2020) - Williams, Vijai; Bansal, Arun; Jayashree, Muralidharan; Ismail, Javed; Aggarwal, Ashish; Gupta, SK; Singhi, Sunit; Singhi, Pratibha; Baranwal, Arun Kumar; Nallasamy, Karthi
Abstract: Purpose: To study the clinical profile and predictors of outcome in children undergoing decompressive craniectomy (DC) for non-traumatic intracranial hypertension (ICH). Materials and methods: Mixed observational study of children, aged 1 month-12 years, who underwent DC for non-traumatic ICH in a tertiary care pediatric intensive care unit from 2012 to 2017. Data on clinical profile and outcome were retrieved retrospectively and survivors were assessed prospectively. The primary outcome was neurological outcome using Glasgow Outcome Scale-Extended (GOS-E) at minimum 6 months' post-discharge. GOS-E of 1–4 were classified as a poor and 5–8 as a good outcome. Results: Thirty children, median (IQR) age of 6.5 (2, 50) months, underwent DC; of which 26 (86.7%) were boys. Altered sensorium ( n = 26, 86.7%), seizures ( n = 25, 83.3%), pallor ( n = 19, 63.3%) and anisocoria ( n = 14, 46.7%) were common signs and symptoms. Median (IQR) Glasgow Coma Scale at admission was 9 (6, 11). Commonest etiology was intracranial bleed ( n = 24; 80%). Median (IQR) time to DC was 24 (24, 72) h. Eight (26.7%) children died; 2 during PICU stay and 6 during follow-up. Neurological sequelae at discharge ( n = 28) were seizures ( n = 25; 89.2%) and hemiparesis ( n = 16; 57.1%). Twenty-one children were followed-up at median (IQR) duration of 12 (6, 54) months. Good neurological outcome was seen in 14/29 (48.2%) and hemiparesis in 10/21 (47.6%) patients. On regression analysis, anisocoria at admission was an independent predictor of poor outcome [OR 7.33; 95%CI: 1.38–38.87; p = 0.019]. Conclusions: DC is beneficial in children with non-traumatic ICH due to a focal pathology and midline shift. Evidence on indications and timing of DC in NTC is still evolving.